Melanoma Prevention Using Topical PBISe - Chung, Chin-Ying (2011)
Malignant melanoma is the deadliest form of skin cancer, known for its drug resistance and high metastatic potential. Deregulated PI3 and MAP kinase pathways promote early melanocytic lesion development and confer drug resistance. No agent exists to target these deregulated pathways to prevent cutaneous non-invasive melanocytic cells or invasive melanomas from developing into more aggressive widely disseminated metastatic disease. In this study, a selenium containing isosteric analogue of PBIT [S,S′-1,4-phenylenebis(1,2-ethanediyl)bis-isothiourea] called PBISe [Se,Se′-1,4-phenylenebis(1,2-ethanediyl)bis-isoselenourea] is shown to moderate these two major signaling pathways to prevent cutaneous melanocytic lesion or melanoma development. Topical application of PBISe retarded melanocytic lesion development in laboratory-generated skin by 70-80% and in animal skin by ∼50%. Mechanistically, prevention of lesion development occurred due to decreased Akt3 signaling, which increased MAP kinase pathway activity to inhibitory levels. The combined effect of targeting these pathways led to decreased cell proliferation and increased apoptotic cell death thereby preventing melanoma development. Thus, topically applied PBISe treatment has potential to prevent non-invasive melanocytic lesion and invasive metastatic melanoma development in skin.